The Association Between Effectiveness of Tinnitus Intervention and Cognitive Function—A Systematic Review - Lan, Tianxiang; Cao, Zuwei; Zhao, Fei; Perham, Nick (Frontiers in Psychology, 2021)
Tinnitus refers to the perception of sound in the absence of an external stimulus. This can be problematic and lead to health problems in some sufferers, including effects on cognitive functions such as attention and memory. Although several studies have examined the effectiveness of tinnitus interventions, e.g., cognitive behavioural therapy and sound therapy, it is still unclear as to the overall quality and limitations of these studies and whether their results could be generalized. Clarification is also needed as to whether poor cognitive function will lead to a less favourable intervention outcome in tinnitus patients. The present systematic review was therefore designed to critically appraise and synthesize findings from randomised controlled trials (RCTs) of tinnitus intervention and its effects on cognition. The methodology followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Medline (PubMed), Embase, and PsycINFO were searched. Only RCTs that compared the effectiveness of a tinnitus intervention and a measure of cognitive function in adult participants with tinnitus were included. A total of eight studies involving 610 participants tested using 11 cognitive function assessment tools (e.g., Stroop Colour and Word Test and Visual Continuous Performance Task) and 5 tinnitus intervention outcome measurements (e.g., Tinnitus Handicap Inventory and Tinnitus Questionnaire) were included and analysed. The outcomes of the review suggest tinnitus intervention not only facilitates tinnitus management but also improves cognitive functions. It is likely that cognition and emotion play an important role in a patient’s adjustment to tinnitus. Whether cognition can predict treatment outcomes is unclear due to insufficient evidence. Future research is needed using a standardised assessment protocol focussing on the effect of sound-based interventions on tinnitus severity and cognitive functions. Studies on whether cognitive function measurement can be used as a predictor for the effectiveness of tinnitus therapy are also needed.